THE ROLE OF PROFESSIONAL COMMITMENT: A THEORETICAL REVIEW OF OCCUPATIONAL STIGMA AND TURNOVER INTENTION - Zhao Yaosong; Ooi Boon Keat (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the impact of occupational stigma on turnover intention among healthcare workers, with a focus on the mediating role of occupational self-esteem. Method: An integrated theoretical framework combining Conservation of Resources (COR) Theory, Social Identity Theory, and the Job Demands-Resources (JD-R) Model was employed to explain the psychological mechanisms underlying this relationship. Occupational stigma was conceptualized as a stressor that depletes personal resources, while occupational self-esteem was examined as a protective factor. Results: The findings reveal that occupational stigma significantly predicts turnover intention, but this effect is mediated by occupational self-esteem. Healthcare workers with higher levels of professional self-worth demonstrated greater resilience against stigma-induced resource depletion, thereby reducing disengagement and turnover intention. Novelty: This research advances the literature by introducing a comprehensive model that explicates how stigma translates into turnover through resource depletion processes and highlights occupational self-esteem as a critical buffer. The study provides actionable implications for healthcare institutions to design retention strategies through resilience-building, recognition systems, and supportive organizational cultures that mitigate stigma and foster employee well-being.